2012
DOI: 10.1182/blood.v120.21.78.78
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Circularly Permuted TRAIL (CPT) for the Treatment of Relapsed or Refractory Multiple Myeloma: An Open-Label, Multicenter Phase II Clinical Trial

Abstract: 78 Background: Circularly permuted TRAIL (CPT) is a recombinant mutant of human Apo2L/TRAIL developed by Beijing Sunbio Biotech Co., Ltd. as a targeted therapy for multiple myeloma and other hematologic malignancies. CPT is a dual pro-apoptotic receptor agonist that directly activates both pro-apoptotic receptors TRAIL-R1 (DR4) and TRAIL-R2 (DR5). CPT selectively induces apoptosis in a variety of cancer cells, while sparing most normal cells in preclinical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Compared with wild‐type Apo2L/TRAIL, CPT has better stability and slightly longer half‐life in mice, rats, and humans, and also displays better antitumor activity without significant toxicity against normal cells . In previous clinical trials , CPT monotherapy was well tolerated in patients with relapsed and/or refractory MM (RRMM), with no dose‐limiting toxicity (DLT) or maximal tolerated dose (MTD) with CPT doses up to 15 mg/kg. Approximately 20–30% of patients achieved partial response (PR) or better.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with wild‐type Apo2L/TRAIL, CPT has better stability and slightly longer half‐life in mice, rats, and humans, and also displays better antitumor activity without significant toxicity against normal cells . In previous clinical trials , CPT monotherapy was well tolerated in patients with relapsed and/or refractory MM (RRMM), with no dose‐limiting toxicity (DLT) or maximal tolerated dose (MTD) with CPT doses up to 15 mg/kg. Approximately 20–30% of patients achieved partial response (PR) or better.…”
Section: Introductionmentioning
confidence: 99%
“…Early preclinical studies evaluating CPT demonstrated its potential anti‐tumoral properties alone and in association with chemotherapy in vitro and in vivo on several tumour types (Fang et al ., ; Tang et al ., 2005; 2008; Zhang et al ., ; Wang et al ., ). A phase Ib dose escalation study (Chen et al ., 2012b) and a phase II multi‐centre open‐label single‐arm study (Chen et al ., 2012c) have been performed on relapsed or refractory multiple myeloma patients. CPT was either given intravenously for 5 consecutive days each 21 days for four cycles with increasing concentrations ranging from 5 to 15 mg·kg −1 per day or administered at 2.5 mg·kg −1 per day for 14 consecutive days of each 21‐day cycle for two cycles.…”
Section: Trail and Derivativesmentioning
confidence: 97%
“…Moreover, CPT exhibited more robust pro-apoptotic activity than dulanermin ( Fang et al, 2005 ). However, patients who were enrolled in the second phases of clinical testing experienced mostly partial responses, whereas novel severe side effects were reported, such as CPT-mediated liver injury ( Chen et al, 2012 ).…”
Section: Recombinant Trailmentioning
confidence: 99%